Updates on Functional Characterization of Bronchopulmonary Dysplasia – The Contribution of Lung Function Testing - Greenough, Anne; Pahuja, Anoop (Frontiers in Medicine, 2015)
Bronchopulmonary dysplasia (BPD) is a chronic lung disease that predominantly affects prematurely born infants. Initially BPD was described in infants who had suffered severe respiratory failure and required high pressure, mechanical ventilation with high concentrations of supplementary oxygen. It now also occurs in very prematurely born infants who initially had minimal or even no signs of lung disease. These differences impact on the nature of the lung function abnormalities suffered by “BPD” infants, which is also influenced by the criteria used to diagnose BPD and the oxygen saturation level used to determine the supplementary oxygen requirement. Key also to interpreting lung function data in this population is whether appropriate lung function tests have been used and in an adequately sized population to make meaningful conclusions. It should also be emphasised that BPD is a poor predictor of long term respiratory morbidity. Bearing in mind those caveats, studies have consistently demonstrated that infants who develop BPD have low compliance and functional residual capacities and raised resistances in the neonatal period. There is, however, no agreement with regard to which early lung function measurement predicts the development of BPD, likely reflecting different techniques were used in different populations in often underpowered studies. During infancy, lung function generally improves, but importantly airflow limitation persists and small airway function appears to decline. Assessment of lung function has demonstrated that improvements in lung function following diuretics or bronchodilators have not translated into long term improvements in respiratory outcomes. In contrast, early differences in lung function related to different ventilation modes have led to investigation and demonstration that prophylactic, neonatal high frequency oscillation appears to protect small airway function.